Molecular characterization of Listeria monocytogenes isolated from foods - Pimenta,Fabiana Cristina (1999)
A total of 30 strains of Listeria monocytogenes isolated from different foods (16 of differents kinds of sausage, 14 cheese,) purchased at groceries of São Paulo City were ribotyped and analysed for the presence and expression of hemolysin gene and production of phosphatidylinositol-specific phosphalipase C - PI-PLC enzyme. The L. monocytogenes strains were differentiated into six ribotype classes. A total of 13 (43.3%) from these strains belong to the same ribotype (ribotype I), and was coincident to the ribotype of the standard L. monocytogenes prototype strain (ATCC-15313). The hemolytic activity was observed in 29 (96.7%) strains when incubated at 37oC, but not at 4oC. The direct colony hybridization method for hemolysin gene detection showed a positive reaction whit all the 30 L. monocytogenes strains, while showed negative reaction with other Listeria spp. The PI-PLC was produced by 27 (90%) of the strains analysed. There was no correlation between the six identified ribotypes and the virulence factors (hemolysin and PI-PLC) studied.